Synthese neuer Nonafulvene - Gabriele Sabbioni; Albin Otter; Markus Neuenschwander (CHIMIA)
A series of new nonafulvenes 1b-1g have been prepared by means of 3 synthetic procedures. The 1H-NMR-spectra of compounds 1b-1g have been analysed and assigned at 400 Mc.